Column Generation Based Algorithm for Service Chaining Relaxing Visit Order and Routing Constraints - Sato, Takehiro; Kikuchi, Atsushi; Shinkuma, Ryoichi; Oki, Eiji (IEEE Global Communications Conference (Online), 2020)
Service chaining is a method for providing desired network services to users by concatenating virtualized network functions (VNFs) in the network. There have been studies on service chain provisioning models that relax the visit order of VNFs and routing constraints. These models make it difficult to obtain an optimal solution in a practical time due to the huge number of decision variables associated with the problem. A heuristic approach that obtains a nearly-optimal solution within a practical time is needed. This paper proposes a column generation based heuristic algorithm for the service chain provisioning problem that relaxes the VNF visit order and routing constraints. The proposed algorithm divides the problem into a VNF placement problem and a routing problem and applies the column generation technique to solve the latter. Numerical results show that the proposed algorithm shortens the computation time compared to directly solving the original integer linear programming problem in exchange for some increase in the cost for VNF placement and link utilization.